تقييم أداء طرق تشخيص اعتلال الشبكية السكري - بليلو, محمد (Latakia University Journal -Engineering Sciences Series, 2017)
يعتبر تشخيص الأمراض باستخدام معالجة الصور من أهم المجالات التي تستخدم تقنيات معالجة الصورة في المجال الطبي حيث تعد البيانات الرقمية في مجال طب العيون محور تركيز الباحثين للكشف التلقائي عن بعض الأمراض الهامة كاعتلال الشبكية السكري (DR) و يٌّعرف بأنه تلف في شبكية العين يأتي نتيجة الاختلاطات و المضاعفات الخطيرة على الجسم البشري الناتجة عن مرض السكري على المدى الطويل و يعتبر أحد أهم الأسباب المؤدية للعمى في العالم و يسبب اضرارا خطيرة لشبكية العين.يهدف البحث إلى تقييم أداء بعض الطرق المتبعة في تشخيص اعتلال الشبكية السكري من خلال الكشف عن إحدى أهم الآفات المرافقة له في شبكية العين و هي الإفرازات و ذلك عبر تشخيصها في صور قاع العين الرقمية من خلال تقنيات معالجة الصورة حيث تساهم عملية الكشف هذه في المساعدة على الكشف المبكر عنه.Considered the diagnosis of diseases using image processing is one of the most important areas of image processing techniques used in the medical field, Where is the digital data in the field of ophthalmology focus of researchers for automatic detection of some important diseases such as diabetic retinopathy (DR).And is defined as damage to the retina of the eye comes as serious complications and on the human body complications resulting from diabetes in the long term and is considered one of the most important causes of blindness in the world and cause serious damage to the retina.The research aims to Assess the performance of some of the methods used in the diagnosis of diabetic retinopathy by revealing one of the most important accompanying pests him in the retina of the eye and is the exudates and through diagnosed in images digital fundus through image processing techniques where this detection process contributes in helping to early detection.